Pastures valorisation: Tools and effects - Gaki D.; Faraslis I.; Hadjigeorgiou I. (Ecosystem services and socio-economic benefits of Mediterranean grasslands, 2016)
Pastures in Greece, as a public good, contributed through the ages to the development of efficient small ruminants farming systems and the formation and preservation of the local ecosystems. The shift of this type of livestock farming towards specialization in milk production was based on the abundant use of concentrate feedstuff. This increased milk productivity also contributed to the degradation of traditional pastures. The new Common Agricultural Policy period raises again the importance of pastoral resources. In this paper the methodological chain (advanced technological tools – innovated methods) that we have developed in order to response to the issues of land pastures’ degradation and management are presented. The results of a research in the Region of Thessaly demonstrated that pastures renovation should be based both in the involvement of all stakeholders, as well as on the use of modern technology which will contribute to rational valorisation. Improving grazing capacity of pastureland helps to increase farm productivity and improve farm income through reducing animal feeding costs and adding value through an environmental friendly system of production. The existence of a favourable political framework and appropriate tools provides guarantees to the local rural communities for negotiate and decide the appropriate management of their pastureland aimed their sustainability.
15. Meeting of the Mediterranean Sub-Network of the FAO-CIHEAM International Network for the Research and Development of Pastures and Fodder Crops, 2016/04/12-14, Orestiada (Greece)